(untitled) (Móin-Móin Magazine - Studies in the Art of Puppetry, 2021)
Abstract: El Pequeño Museo Virtual de la Cuarentena is a web page opened in November 2020 during the pandemic, as a place for experimentation and creation. It was done by the La Compañía Inestable de Estudiantes of the Focalización en Teatro de títeres y Objetos, Universidad Nacional de San Martín, UNSAM, Argentine. The proyect wanted to change the perception and lecture of the intimate space during the lockdown of the sanitary emergency, as a way to make this space became a land to discover histories.